Core Processes: How to Use Evidence, Theories, and Research in Planning Behavior Change Interventions - Ruiter, Robert A. C.; Crutzen, Rik (Frontiers in Public Health, 2020)
Psychology is not only a basic behavioral science but also an applied discipline that is used to solve societal problems. In a problem-driven context, the search for existing literature, the correct application of appropriate theories, and the collection of additional research data are basic tools essential for the systematic development of any theory- and evidence-based behavior change intervention. The processes of brainstorming, literature review, theory selection and application, and data collection are “Core Processes” that can be used in different phases/steps of intervention planning—from needs assessment to intervention design to program implementation and evaluation—and within different planning frameworks. In this paper, we illustrate how the use of these “Core Processes” provides expert, empirical and theoretical guidance to planners from problem definition to problem solution. Specific emphasis is put on finding theories that are potentially useful in providing answers to planning questions using a combination of approaches to access and select theories (i.e., the topic, concept, and general theories approaches). Furthermore, emphasis is put on the logic of answering planning questions in a specific order by first brainstorming before consulting the literature, then applying theories, and finally collecting additional data.